Covid 19 döneminde aile işletmelerindeki yöneticilerin nesiller arası bireysel değer farklılıkları üzerine bir araştırma - AŞKUN, OLCAY BİGE (My University, 2022)
Pandemi sürecinin uzun bir döneme yayılması ve etkilerinin halen devam etmesi sebebiyle her alanda değişimler olmuştur. Bireylerin davranışlarına yön veren değer yapılarının da bu değişimlerden etkilenebileceğinden söz edilmektedir. Bu doğrultuda değerler önemli hale gelmektedir. Bu çalışmanın amacı; aile işletmelerindeki yöneticilerde nesiller arası değer farklılıklarının olup olmadığının araştırılması ve eğer farklılık var ise hangi değer yapıları arasında olduğunun değerlendirilmesidir. Araştırma örneklemi, Marmara Bölgesi’nde faaliyette bulunan aile işletmelerinde farklı nesillerden toplam 631 yöneticiden oluşmaktadır. Araştırma bulguları Covid 19 pandemisi gibi belirsizlik ve kriz yönetiminin öne çıktığı koşullara karşı bireysel değerlerin önemli bir rolü olduğunu ortaya koymaktadır. Araştırma kapsamında incelenen bireysel değer boyutlarında nesiller arasında farklılıkların olduğu sonucuna ulaşılmıştır. Pandemiyi kontrol etme ya da önleme gibi hususlarda bireylerin yardımseverlik, uyumluluk, toplum yanlılığını içeren evrensellik gibi değer eğilimlerinin öne çıktığı gözlenmiştir. Ayrıca çalışma yaşamı içerisinde nesiller arası değer farklılıklarının kabul edilerek, farklı beklentilerin ve iş yapış şekillerinin incelenmesinin ilgili literatüre katkı sağlayabileceği düşünülmektedir.

There have been changes in every field due to the fact that the pandemic process has spread over a long period and its effects are still continuing. It is mentioned that the value structures that direct the behaviors of individuals may also be affected by these changes. In this direction, it becomes important to examine the values. The aim of this study is to investigate whether there are value differences between generations of managers in family businesses and, if there is, to evaluate which value structures they are between. The research sample consists of a total of 631 managers from different generations in family businesses operating in the Marmara Region. Research findings reveal that individual values play an important role in conditions where uncertainty and crisis management come to the fore, such as the Covid 19 pandemic. It has been concluded that there are differences between generations in the individual value dimensions examined within the scope of the research. It has been observed that in matters such as controlling or preventing the pandemic, value tendencies of individuals such as benevolence, compatibility, universality including social bias have come to the fore. In addition, it is thought that by accepting the value differences between generations in working life, examining different expectations and ways of doing business can contribute to the relevant literature.
A research on intergenerational individual values differences of managers in family business in the period of covid 19
Keywords: Bireysel Değerler; Aile İşletmeleri; Nesiller Arası Farklılıklar; Individual values; Family businesses; Generational differences